2002
DOI: 10.1002/art.10547
|View full text |Cite
|
Sign up to set email alerts
|

Significant increases in serum and plasma concentrations of matrix metalloproteinases 3 and 9 in patients with rapidly destructive osteoarthritis of the hip

Abstract: Objective. Rapidly destructive osteoarthritis (OA) of the hip is an uncommon subset of OA that affects mainly elderly women. Previous studies indicate that elevated levels of matrix metalloproteinases (MMPs) are produced within the tissue of patients with the condition. In the present study, we sought to determine whether serum and plasma levels of MMPs and tissue inhibitors of metalloproteinases (TIMPs) are also elevated.Methods. Blood samples were obtained from 16 patients with rapidly destructive hip OA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 34 publications
3
56
1
1
Order By: Relevance
“…KHC3081, KHC3061, KHC1491 and KHC3081, respectively; Thermo Fisher Scientific, Inc., Waltham, MA, USA). In each assay, the proactive and active forms of both MMP-2 and -9 were processed according to the manufacturer's instructions, as previously described (14,15). Prior to analysis, the samples were thawed briefly in a 37˚C water bath and placed on ice.…”
Section: Methodsmentioning
confidence: 99%
“…KHC3081, KHC3061, KHC1491 and KHC3081, respectively; Thermo Fisher Scientific, Inc., Waltham, MA, USA). In each assay, the proactive and active forms of both MMP-2 and -9 were processed according to the manufacturer's instructions, as previously described (14,15). Prior to analysis, the samples were thawed briefly in a 37˚C water bath and placed on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue and circulating concentrations of MMPs are elevated in patients with OA [20,21]. Observational human studies showed vitamin D status to be inversely associated with circulating MMP9 in healthy adults, while vitamin D 3 supplementation (3 monthly injections of either 500 IU or 50 000 IU) reduced MMP9 concentrations in adults with vitamin D insufficiency [22].…”
Section: Potential Of Vitamin D To Influence Cartilage Homeostasismentioning
confidence: 99%
“…Enfin, Masuhara une coxarthrose d'évolution lente [23]. Ces deux résultats reflètent la sévérité de la chondrolyse et l'intensité de l'activité protéasique dans la CDR.…”
Section: Signes Biologiquesunclassified